Komunikasi Dalam Persepektif Islam - Syawal Syawal; Ismaya Ismaya; Andi Ahmad Chabir Galib; Ushwa Dwi Masrurah Arifin Bando; Elihami Elihami; M Yunus Sudirman (EduPsyCouns: Journal of Education, Psychology and Counseling, 2022)
Abstract: Communication always continues to grow, by giving birth to various theories and principles. The term communication has been widely written with an emphasis on diverse foci. The diversity of understanding is due to different perspectives in viewing communication as a social phenomenon. From an Islamic perspective, we can answer that it was Allah who first taught us to communicate using reason and language skills that He gave us (ar-Rahman 1-4). The primary source of Islamic communication is the Al-Quran and Hadith, so one of the benefits of Islamic communication is that it brings us closer to the truth of God, because the source comes from Allah SWT himself. Furthermore, because we know that all aspects of life are actually inseparable from the demands of the Qur'an and hadith. Abstrak: : Komunikasi senantiasa terus berkembang, dengan melahirkan berbagai macam teori-teori dan prinsip-prinsipnya. Istilah komunikasi telah banyak ditulis dengan menekankan pada fokus yang beragam. Keragaman pengertian tersebut disebabkan perbedaan perspektif dalam melihat komunikasi sebagai fenomena sosial. Dari perspektif islam, kita bisa menjawab bahwa Allah yang lebih dulu mengajari kita untuk berkomunikasi dengan menggunakan akal dan kemampuann bahasa yang dianugrahkan-Nya kepada kita (ar-Rahman 1-4). Sumber primer komunikasi islam adalah Al-Quran dan Hadits, maka salah satu manfaat komunikasi islam adalah mendekatkan kita kepada kebenaran Tuhan, karena sumbernya berasal dari Allah SWT sendiri. Selanjutnya karena kita tahu bahwa semua aspek kehidupan ini sebenarnya tidak terlepas dari tuntutan al-qur’an dan hadits.